2003
DOI: 10.17660/actahortic.2003.614.93
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and Estimation of Transpiration of a Soilless Rose Crop and Application to Irrigation Management

Abstract: A mis Directores, por el apoyo incondicional y confianza en mi a lo largo del desarrollo de esta Tesis. Especial agradecimiento a Pedro-Florián Martínez García, Investigador Principal del Departamento de Horticultura del IVIA, co-director de esta Tesis, director experimental de la misma, responsable del equipo de investigación en el que me encuentro, por enseñarme y facilitarme el aumento del conocimiento en el ámbito de trabajo. Claro defensor del trabajo en equipo y catalizador de la participación activa de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 8 publications
1
14
1
1
Order By: Relevance
“…"Dallas" can be done using a linear function based only on stem height. The model developed in our study presented a higher R 2 (R 2 = 0.95, n = 26) than the value obtained by Suay et al [19], although a lower number of observations were used. These authors also concluded that only 11 stems were needed to estimate the LA of the flowering shoots with an error of less than 5%.…”
Section: Resultscontrasting
confidence: 59%
See 4 more Smart Citations
“…"Dallas" can be done using a linear function based only on stem height. The model developed in our study presented a higher R 2 (R 2 = 0.95, n = 26) than the value obtained by Suay et al [19], although a lower number of observations were used. These authors also concluded that only 11 stems were needed to estimate the LA of the flowering shoots with an error of less than 5%.…”
Section: Resultscontrasting
confidence: 59%
“…According to Suay et al [19], the estimation of stem LA in cut roses of the cv. "Dallas" can be done using a linear function based only on stem height.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations